Firm Level Competitiveness of Small and Medium Enterprises (SMEs): Analytical Framework Based on Pillars of Competitiveness Model - Wisenthige, Krishantha; Guoping, Cheng (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The research on competitiveness has been increasing in popularity amongst scholars, there is a lack of studies focusing on the firm level competitiveness of Small and Medium Enterprises (SME). The objective of this paper is to develop a framework model, which can be used to analyze the competitiveness of the SME at the firm level. In this paper, we propose a framework of six pillars of competitiveness, which constitute the physical and human resources, innovation, networking, management processes as well as customers (demand conditions) and competitors (supply conditions). The methodology is unique in the sense that it incorporates the unique analytical framework called the bottlenecks over the pillars of competitiveness, which calculate the individual level competitiveness points for each SME and competition points that can collate significantly with the selected measures of competitiveness. This comprehensive framework needs to be tested empirically with the data in future research.